ChemInform Abstract: An Unexpected Rearrangement—Hydration Reaction Sequence of 2H‐Chromenes to Dihydrochalcones under Catalysis of HAuCl4. Issue 12 (14th March 2013) - Maiti, Gourhari; Kayal, Utpal; Karmakar, Rajiv; Bhattacharya, Rudraksha N.
Abstract A simple protocol is developed for the conversion of various substrates into highly functionalized propanone frameworks.